Microstructure and Compressive Peak Stress Analyses of 3D Printed TPU MM-3520 - Ameen, Ahmed; Takhakh, Ayad; Abdal-hay, Abdalla (Al-Nahrain Journal for Engineering Sciences, 2024)
Specimens with the structure of a face-centered cubic were produced using several sets of printing conditions. An experimental testing is conducted to carefully evaluate the microstructural analysis and compressive strength of this structure. The results include the measurement of mechanical properties, such as the peak stress. Fused deposition modeling is employed for the additive manufacturing of experimental specimens made from shape memory polymer thermoplastic polyurethane (MM-3520). We take into account the impact of printing factors on lattice structures, such as layer thickness, printing temperature, and printing speed. Analyzing the microstructure of the printed specimens exhibits that the specimens with highest printing temperature, lowest printing speed and thinner printing layer have better layers adhesion and lower porosities. All the mechanical tests are performed on specimens with the same structure and at a relatively constant density. Among the tested printing parameters, using a layer height of 0.1 mm, a printing temperature of 230 °C, and a printing speed of 20 mm/s yields the highest strength in the specimens. However, specimens printed with a layer height of 0.2 mm, a printing temperature of 220 °C, and a printing speed of 30 mm/s also exhibit good strength, albeit slightly lower than the maximum values. Additionally, when using these specific settings (0.3 mm – 210 °C – 40 mm/s), the mechanical qualities are minimized, yet the stress-strain curves exhibit characteristics similar to elastomers.